The Effect of Kangaroo Mother Care Counseling on Postpartum Blues, A Randomized Clinical Trial - Fatemeh Shobeiri; Somaieh Hajian; Zahra Massoumi; Alireza Soltanian (Hamadan University of Medical Sciences, 2018)
Introduction: Kangaroo mother care is a standard method based on skin contact with the mother and newborn skin. The aim of this study was to evaluate the effect of kangaroo mother care counseling on postpartum blues in women in Fatemieh Hospital, Hamadan. Methods: A randomized clinical trial was conducted on 104 pregnant women who referred to Fatemieh hospital in Hamadan city, 2016. Those who had gestational age of 37-42 weeks were randomly divided in to two groups of case and control according to the day of delivery. Postpartum routine care was performed in both groups. In the case group in first 24 hours after delivery, kangaroo mother care was taken with a counseling session (20-30 minutes) was performed until the 10th day of delivery. The after birth Stein questionnaire was completed before and after intervention in two groups. Data was analyzed using SPSS16, t-test and ANOVA. Results: The results showed that the intervention in the experimental group was about 4 times lower in postpartum distress score (P <0.001). However, the control group also had a significant decrease on the 10th day before the intervention, but this decrease was higher in the experimental group (P = 0.009). Conclusion: The results showed that kangaroo mother care could reduce the postpartum blues. Mother's kangaroo care after delivery is recommended to promote benefits for mother and baby.